Method for preparing aluminum alloy spherical powder for negative electrode of aluminum secondary battery by atomization method
The preparation of aluminum alloy spherical powder by atomization method solves the irreversibility and dendrite problems of the negative electrode of aluminum secondary batteries, improves the cycle stability and rate performance of the battery, and realizes the high-performance application of aluminum secondary batteries.
Patent Information
- Application Number
- CN202411294069.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
The poor reversibility of aluminum secondary batteries is mainly due to the irreversibility problem of aluminum negative electrodes, which leads to poor cycle stability, short life and low capacity. In addition, traditional aluminum foil negative electrodes produce dendrites under high currents, causing safety hazards.
Aluminum alloy spherical powder is prepared by atomization method as the negative electrode material of aluminum secondary battery. Micron-scale aluminum alloy spherical powder is obtained through mixed smelting and atomization processes, and alloy elements are evenly distributed to reduce the passivation of aluminum metal surfaces and improve aluminum ions. transmission dynamics.
It significantly improves the electrochemical stability and cycle performance of aluminum secondary batteries, enhances the peeling/electroplating kinetics of aluminum, extends the cycle life of the battery, and improves the rate performance.
Smart Images

Figure CN119140831A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a method for preparing aluminum alloy spherical powder for negative electrodes of aluminum secondary batteries by an atomization method. Background Art
[0002] Aluminum secondary batteries have become a promising candidate material to replace lithium batteries due to their low cost, high abundance, and high safety of non-flammable electrolytes. Aluminum not only has the lowest cost compared to other metals (the price is only 1 / 150 of the price of metallic lithium), but is also the third most abundant element in the earth's crust. The cation radius of aluminum ions is small and has good transport kinetics. Aluminum also has a higher electronegativity and is safer in air and moisture. From the perspective of energy storage, aluminum secondary batteries can provide an electrochemical reaction of three electron transfer, providing 2980mAh·g -1 The highest gravimetric capacity and 8046 mAh cm -3 Therefore, rechargeable aluminum-based batteries also have broad prospects in grid-type energy storage applications and are the development direction of large-scale energy storage technology in the post-lithium battery era.
[0003] Limited by the extremely strong acidity of ionic liquid electrolytes, room temperature ionic liquid electrolytes containing chlorine will destroy electrode components, and the strong interaction between Al-Cl will limit the application of high-performance positive electrode materials, threatening the actual cycle life of aluminum secondary batteries. These problems have promoted the development of aqueous electrolytes represented by aluminum trifluoromethanesulfonate. Although positive electrode materials such as titanium oxide, molybdenum oxide, aluminum manganese oxide and Prussian blue analogs show good reversible storage potential for aluminum secondary batteries in aqueous electrolytes, the reversibility of aluminum secondary batteries is still poor even with aluminum trifluoromethanesulfonate electrolytes, mainly due to the irreversibility of aluminum negative electrodes.
[0004] In aluminum secondary battery systems, high-purity aluminum foil is generally used directly as the negative electrode material. However, the oxide insulating layer covering its surface will hinder the Al 3+ The stripping / plating kinetics of Al / Al 3+ The redox potential is low, and the precipitation potential is much more negative than the hydrogen precipitation potential, which makes the hydrogen evolution reaction of aluminum secondary batteries serious, with more by-products, poor reaction reversibility, cycle stability, short life, low capacity and other problems. In addition, during the frequent aluminum plating and dealuminizing process on its surface, after a long period of accumulation, due to the influence of concentration polarization, a large number of aluminum dendrites are inevitably generated. These aluminum dendrites cause the battery capacity to decay rapidly and may even pierce the diaphragm, causing a safety hazard of battery short circuit. Therefore, there is an urgent need to explore simple and universal strategies to develop new aluminum-based negative electrode materials for high-performance aluminum secondary batteries with enhanced aluminum reversibility.
[0005] Although the passivation problem can be alleviated by alloying or by constructing an artificial solid electrolyte interphase, the inevitable side reactions will seriously hinder the reversible energy storage of aqueous Al metal batteries. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing aluminum alloy spherical powder for the negative electrode of aluminum secondary batteries by atomization. The present invention obtains micron-sized aluminum alloy spherical powder as the negative electrode material of aluminum secondary batteries by atomization process to treat alloy ingots, which can not only effectively improve the electrochemical stability of the negative electrode material, but also the battery exhibits excellent long cycle performance and excellent rate performance.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] The present invention first provides a method for preparing aluminum alloy spherical powder for aluminum secondary battery negative electrode by atomization method, comprising the following steps:
[0009] S1. According to the target composition of the aluminum alloy, various metal ingots in the aluminum alloy are mixed and smelted to obtain a molten aluminum alloy liquid;
[0010] S2, atomizing the molten aluminum alloy liquid, cooling and solidifying the formed fine droplets, and then sieving to obtain aluminum alloy spherical powder. The large-particle alloy powder that does not meet the size requirements after sieving can be returned to the furnace for melting.
[0011] Furthermore, the aluminum alloy comprises the following components in atomic percentage: Al 60-100%, M 0-40%, wherein M is one or more of Zn, Li, Mg, Fe, Si, Mn, La, Ce, Pr, Nd, Y and Sc.
[0012] Furthermore, in step S1, the smelting is carried out under vacuum, the melt temperature is 650-800°C, and the smelting time is 1-2h.
[0013] Furthermore, in step S2, the atomization method is: the molten aluminum alloy liquid flows into the atomization nozzle through the guide pipe, and is impacted by the high-pressure gas at the atomization nozzle to form fine droplets, and the formed fine droplets are quickly cooled and solidified into aluminum alloy spherical powder. The atomization method can make the various elements of the aluminum alloy negative electrode material evenly distributed, which is conducive to the transmission of aluminum ions and reduces the passivation of the aluminum metal surface.
[0014] Furthermore, the diameter of the flow guide tube is 3-7 mm, the flow rate of the molten aluminum alloy liquid is 10-15 g / s; the flow rate of the high-pressure gas is 25 m / s. 3 / h~30m 3 / h, the atomization pressure is 2.0MPa-3.0MPa, and the gas medium used is one of nitrogen, argon and helium; the cooling rate of the cooling solidification is 60-102℃ / s.
[0015] The aluminum alloy spherical powder prepared by the method has a micron-level spherical particle morphology, a spherical rate higher than 95%, a particle size of 3 to 100 μm, less bonding, and a density of 1.5 to 3.5 g / cm3 measured by a full-automatic true density tester. 3 .
[0016] The present invention also provides an aluminum secondary battery, wherein the negative electrode active material of the aluminum secondary battery adopts the above-mentioned aluminum alloy spherical powder.
[0017] Further: the aluminum alloy spherical powder material is mixed with a conductive agent and a binder in a solvent, and ground evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a current collector, and dried to obtain an aluminum secondary battery negative electrode; or the negative electrode slurry is dried and then pressed into a sheet to obtain an aluminum secondary battery negative electrode. The conductive agent can be selected from one of Ketjen black, carbon black and acetylene black, the binder can be selected from polyvinylidene fluoride or polytetrafluoroethylene, and the solvent can be selected from N-methylpyrrolidone. The mass ratio of the aluminum alloy spherical powder, the conductive agent, the binder and the solvent is 70-80:5-10:5-20:150-300. The current collector can be selected from one of stainless steel foil, titanium foil, copper foil and nickel foil. The drying temperature is 80-100°C and the drying time is 6-8h.
[0018] Furthermore, the aluminum secondary battery comprises a negative electrode, a positive electrode, a separator and an electrolyte. The electrolyte can be selected from one of an aqueous solution of aluminum trifluoromethanesulfonate, an aqueous solution of aluminum perchlorate and an aqueous solution of aluminum sulfate, wherein the aluminum salt is dissolved in deionized water with a concentration of 0.5 to 2.5M.
[0019] The above-mentioned numerical range of the present invention includes not only the point values listed above, but also any point values between the above-mentioned numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] In order to overcome the problems of unstable electrochemical performance and poor cycle performance caused by the presence of the traditional aluminum metal negative electrode oxide layer, as well as the dendrite problem generated by flat aluminum foil (Al foil) as the negative electrode of aluminum ion battery under large current and long cycle, the present invention designs an aluminum alloy negative electrode with high reversibility, reduces the passivation of the aluminum metal surface by introducing alloy elements, and obtains micron-sized aluminum alloy balls with uniform distribution of various elements by using an atomization process as the negative electrode material of aluminum secondary battery, thereby enhancing the stripping / electroplating kinetics of aluminum, improving the electrochemical reversibility of aluminum secondary battery, and effectively improving the electrochemical stability of the negative electrode material of aluminum secondary battery. The aluminum secondary battery prepared by using the aluminum alloy negative electrode material provided by the present invention shows excellent long cycle performance and rate performance, which is conducive to the commercial development and application of aluminum secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 X-ray diffraction patterns of aluminum-zinc alloy microspheres (atomic ratios of 100:0, 90:10, and 80:20, respectively) prepared in Examples 1, 2, and 3 of the present invention compared with aluminum foil (Al foil) and aluminum and zinc standard cards;
[0023] Figure 2 The scanning electron microscope image of the aluminum microsphere prepared in Example 1 of the present invention, (a) and (b) correspond to different magnifications;
[0024] Figure 3 This is a scanning electron microscope image of the aluminum-zinc alloy microsphere (atomic ratio of 90:10) prepared in Example 2 of the present invention, where (a) and (b) correspond to different magnifications;
[0025] Figure 4 The scanning electron microscope energy spectrum of the aluminum-zinc alloy microsphere (atomic ratio of 90:10) prepared in Example 2 of the present invention, wherein (a) corresponds to the scanning electron microscope, (b) and (c) correspond to the distribution of Al and Zn elements, respectively;
[0026] Figure 5 This is a scanning electron microscope image of the aluminum-zinc alloy microsphere (atomic ratio of 80:20) prepared in Example 3 of the present invention, where (a) and (b) correspond to different magnifications;
[0027] Figure 6 The scanning electron microscope energy spectrum of the aluminum-zinc alloy microsphere (atomic ratio of 80:20) prepared in Example 3 of the present invention, wherein (a) corresponds to the scanning electron microscope, (b) and (c) correspond to the distribution of Al and Zn elements, respectively;
[0028] Figure 7 This is a scanning electron microscope image of the aluminum-magnesium-lithium alloy microsphere (atomic ratio of 50:45:5) prepared in Example 4 of the present invention, where (a) and (b) correspond to different magnifications;
[0029] Figure 8 The battery assembled with aluminum microspheres (Al powder) and aluminum foil (Al foil) as a comparison in Example 1 of the present invention at room temperature and 0.2 mA / cm -2 Cyclic test diagram under current density (a in the figure corresponds to the electrolyte aluminum perchlorate aqueous solution, and b in the figure corresponds to the electrolyte aluminum trifluoromethanesulfonate aqueous solution);
[0030] Fig. 9 The battery assembled with aluminum-zinc alloy (atomic ratio of 80:20) and aluminum foil (Alfoil) as a comparison in Example 3 of the present invention at room temperature and 0.05 mA / cm -2 Cyclic test diagram under current density (a in the figure corresponds to the electrolyte aluminum perchlorate aqueous solution, and b in the figure corresponds to the electrolyte aluminum trifluoromethanesulfonate aqueous solution);
[0031] Fig.10 The battery assembled with the aluminum-zinc alloy (atomic ratio of 90:10) in Example 2 and the aluminum-zinc alloy (atomic ratio of 80:20) in Example 3 and the aluminum foil (Al foil) as a comparison was tested at room temperature and 0.2 mA / cm -2 Cyclic test diagram under current density, corresponding to aluminum perchlorate electrolyte;
[0032] Fig.11 The battery assembled with the aluminum-zinc alloy (atomic ratio of 90:10) in Example 2 and the aluminum-zinc alloy (atomic ratio of 80:20) in Example 3 and the aluminum foil (Al foil) as a comparison was tested at room temperature and 0.2 mA / cm -2 Cyclic test diagram under current density, corresponding to aluminum trifluoromethanesulfonate electrolyte;
[0033] Fig.12 The figure is a rate performance test diagram of a battery assembled with the aluminum-zinc alloy (atomic ratio of 90:10) in Example 2, the aluminum-zinc alloy (atomic ratio of 80:20) in Example 3 and an aluminum foil (Al foil) as a comparison at room temperature;
[0034] Fig.13 The charge and discharge curve of the button cell assembled with aluminum-zinc alloy (atomic ratio of 90:10) in Example 2 at room temperature and a current density of 100 mA / g;
[0035] Fig.14 This is the charge and discharge curve of the button cell assembled with aluminum-zinc alloy (atomic ratio of 80:20) in Example 3 at room temperature and a current density of 100 mA / g. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described in detail below in conjunction with the drawings in the specific implementation manner and embodiments.
[0037] Example 1
[0038] In this embodiment, pure aluminum spherical powder is prepared by atomization method and used for the negative electrode of aluminum secondary battery. The specific steps are as follows:
[0039] S1. Place the aluminum ingot in a vacuum melting furnace for melting at a melt temperature of 700°C for 1 hour to obtain pure aluminum liquid.
[0040] S2. The aluminum liquid flows into the atomizing nozzle through the guide tube. It is broken and dispersed into fine droplets of different sizes by the impact of high-pressure gas at the atomizing nozzle. The formed fine droplets are quickly cooled and solidified into aluminum spherical powder. The specific conditions are: the diameter of the guide tube is 3mm, the aluminum liquid flow rate is 10g / s; the high-pressure gas flow rate is 25m 3 / h, the atomization pressure is 2.0MPa, the gas medium used is argon; the cooling rate of cooling and solidification is 80℃ / min. Aluminum microspheres are obtained through a mechanical sieving machine and an air flow separator.
[0041] S3. Mix aluminum microspheres with polyvinylidene fluoride and Ketjen black, add solvent N-methylpyrrolidone, and the mass ratio is 80:6:6:200, grind and mix in an agate mortar to obtain a negative electrode slurry; evenly coat the negative electrode slurry on a stainless steel foil with a coating density of 0.3 mg / cm -2 , and dried at 80°C for 8 h to obtain an electrode sheet.
[0042] The X-ray diffraction pattern of the aluminum microspheres prepared in this example is as follows: Figure 1 As shown in the figure, the peaks at 38.473°, 44.722°, 65.099° and 78.232° correspond to the (111), (200), (220) and (311) crystal planes of Al, respectively. The results show that the aluminum powder material was successfully synthesized.
[0043] The scanning electron microscope image of the aluminum microspheres prepared in this example is as follows: Figure 2 As shown in the figure, it can be seen that the aluminum powder is spherical in shape, the sphericity is greater than 98%, the particle size is 5 to 30 μm, the surface is clean and smooth, and there is no serious segregation in the metallographic structure.
[0044] Example 2
[0045] In this embodiment, aluminum-zinc alloy spherical powder (atomic ratio of 90:10) is prepared by atomization method and used for the negative electrode of aluminum secondary battery. The specific steps are as follows:
[0046] S1. Mix aluminum ingots and zinc ingots according to a stoichiometric ratio of 90:10 and place them in a vacuum melting furnace for melting. The melt temperature is 700° C. and the melting time is 1.5 h to obtain a pure aluminum-zinc alloy liquid.
[0047] S2. The aluminum-zinc alloy liquid flows into the atomizing nozzle through the guide tube. It is broken and dispersed into fine droplets of different sizes by the impact of high-pressure gas at the atomizing nozzle. The formed fine droplets are quickly cooled and solidified into aluminum-zinc alloy spherical powder. The specific conditions are: the diameter of the guide tube is 3mm, the flow rate of the zinc alloy liquid is 10g / s; the flow rate of the high-pressure gas is 25m 3 / h, the atomization pressure is 2.0MPa, the gas medium used is argon; the cooling rate of cooling and solidification is 80℃ / min. Through a mechanical sieving machine and an airflow separator, aluminum-zinc alloy micron balls (atomic ratio of 90:10) are obtained.
[0048] S3. Mix aluminum-zinc alloy microspheres (atomic ratio of 90:10) with polyvinylidene fluoride and Ketjen black, add solvent N-methylpyrrolidone, and grind and mix in an agate mortar to obtain a negative electrode slurry; evenly coat the negative electrode slurry on a stainless steel foil with a coating density of 0.3 mg / cm -2 , and dried at 80°C for 8 h to obtain an electrode sheet.
[0049] The X-ray diffraction pattern of the aluminum-zinc alloy microspheres (atomic ratio of 90:10) prepared in this example is as follows: Figure 1 As shown in the figure, the peaks at 38.473°, 44.722°, 65.099° and 78.232° correspond to the (111), (200), (220) and (311) crystal planes of Al, respectively, and the peaks at 36.342°, 43.472°, 54.581° and 70.176° correspond to the (002), (101), (102) and (103) crystal planes of Zn, respectively. The results show that the aluminum-zinc alloy was successfully synthesized.
[0050] The scanning electron microscope image of the aluminum-zinc alloy microsphere (atomic ratio of 90:10) prepared in this embodiment is as follows: Figure 3 As shown in the figure, it can be seen that the aluminum-zinc alloy (atomic ratio is 90:10) presents a spherical shape, the sphericity is greater than 98%, the particle size is 5 to 30 μm, and there is no serious segregation in the metallographic structure.
[0051] The scanning electron microscope energy spectrum of the aluminum-zinc alloy microsphere (atomic ratio of 90:10) prepared in this example is as follows: Figure 4 As shown in the figure, it can be seen that the aluminum and zinc elements are evenly distributed in the aluminum-zinc alloy material synthesized by atomization treatment.
[0052] Example 3
[0053] In this embodiment, aluminum-zinc alloy spherical powder (atomic ratio of 80:20) is prepared by atomization method and used for the negative electrode of aluminum secondary battery. The specific steps are as follows:
[0054] S1. Mix aluminum ingots and zinc ingots according to a stoichiometric ratio of 80:20 and place them in a vacuum melting furnace for melting. The melt temperature is 700° C. and the melting time is 1.5 h to obtain a pure aluminum-zinc alloy liquid.
[0055] S2. The aluminum-zinc alloy liquid flows into the atomizing nozzle through the guide tube. It is broken and dispersed into fine droplets of different sizes by the impact of high-pressure gas at the atomizing nozzle. The formed fine droplets are quickly cooled and solidified into aluminum-zinc alloy spherical powder. The specific conditions are: the diameter of the guide tube is 3mm, the aluminum metal liquid flow rate is 10g / s; the high-pressure gas flow rate is 25m 3 / h, the atomization pressure is 2.0MPa, the gas medium used is argon; the cooling rate of cooling and solidification is 80℃ / min. Through a mechanical sieving machine and an air flow separator, aluminum-zinc alloy micron balls (atomic ratio of 80:20) are obtained.
[0056] S3. Mix aluminum-zinc alloy microspheres (atomic ratio of 80:20) with polyvinylidene fluoride and Ketjen black, add solvent N-methylpyrrolidone, and grind and mix in an agate mortar to obtain a negative electrode slurry; evenly coat the negative electrode slurry on a stainless steel foil with a coating density of 0.3 mg / cm -2 , and dried at 80°C for 8 h to obtain an electrode sheet.
[0057] The X-ray diffraction pattern of the aluminum-zinc alloy microsphere (atomic ratio of 80:20) prepared in this example is as follows: Figure 1 As shown in the figure, the peaks at 38.473°, 44.722°, 65.099° and 78.232° correspond to the (111), (200), (220) and (311) crystal planes of Al, respectively, and the peaks at 36.342°, 43.472°, 54.581° and 70.176° correspond to the (002), (101), (102) and (103) crystal planes of Zn, respectively. The results show that the aluminum-zinc alloy was successfully synthesized.
[0058] The scanning electron microscope image of the aluminum-zinc alloy microsphere (atomic ratio of 80:20) prepared in this embodiment is as follows: Figure 5 As shown in the figure, it can be seen that the aluminum-zinc alloy (atomic ratio is 80:20) presents a spherical shape, the sphericity is greater than 98%, the particle size is 5-30μm, and there is no serious segregation in the metallographic structure.
[0059] The scanning electron microscope energy spectrum of the aluminum-zinc alloy microsphere (atomic ratio of 80:20) prepared in this example is as follows: Figure 6As shown in the figure, it can be seen that the aluminum and zinc elements are evenly distributed in the synthesized aluminum-zinc alloy (atomic ratio is 80:20) material.
[0060] Example 4
[0061] In this embodiment, an aluminum-magnesium-lithium alloy spherical powder (atomic ratio of 50:45:5) is prepared by an atomization method and used for the negative electrode of an aluminum secondary battery. The specific steps are as follows:
[0062] S1. Aluminum ingots, magnesium ingots and lithium ingots are mixed in a vacuum melting furnace according to a stoichiometric ratio of 50:45:5 for melting at a melt temperature of 700° C. for 1.5 h to obtain a pure aluminum-magnesium-lithium alloy liquid.
[0063] S2. The aluminum-magnesium-lithium alloy liquid flows into the atomizing nozzle through the guide tube. It is broken and dispersed into fine droplets of different sizes by the impact of high-pressure gas at the atomizing nozzle. The formed fine droplets are quickly cooled and solidified into aluminum-magnesium-lithium alloy spherical powder. The specific conditions are: the diameter of the guide tube is 3mm, the aluminum metal liquid flow rate is 10g / s; the high-pressure gas flow rate is 25m 3 / h, the atomization pressure is 2.0MPa, the gas medium used is argon; the cooling rate of cooling and solidification is 80℃ / min. Through the mechanical screening machine and the air flow separator, the aluminum-magnesium-lithium alloy micron ball is obtained.
[0064] S3. Mix aluminum-magnesium-lithium alloy microspheres with polyvinylidene fluoride and Ketjen black, add solvent N-methylpyrrolidone, and grind and mix in an agate mortar to obtain a negative electrode slurry; evenly coat the negative electrode slurry on a stainless steel foil with a coating density of 0.3 mg / cm -2 , and dried at 80°C for 8 h to obtain an electrode sheet.
[0065] The scanning electron microscope image of the aluminum-magnesium-lithium alloy microsphere (atomic ratio of 50:45:5) prepared in this embodiment is as follows: Figure 7 As shown in the figure, it can be seen that the material is spherical, and the sphericity rate is greater than 95%, the particle size is 5-35μm, and there is no serious segregation in the metallographic structure;
[0066] The electrode materials obtained in the above embodiments were subjected to the following performance tests:
[0067] 1. Symmetrical battery
[0068] The electrode sheets prepared in each embodiment (or aluminum foil for comparison) were assembled into a symmetrical battery in the order of negative electrode shell-electrode sheet-diaphragm-electrolyte-electrode sheet-positive electrode shell, and the electrolyte was a 1M aqueous solution of aluminum perchlorate or a 1M aqueous solution of aluminum trifluoromethanesulfonate. The assembled battery was subjected to a cycle performance test.
[0069] Figure 8The battery assembled with aluminum microspheres (Al powder) in Example 1 was tested at room temperature and 0.2 mA / cm -2 From the cycle test diagram under current density (a in the figure corresponds to the electrolyte aluminum perchlorate aqueous solution, and b in the figure corresponds to the electrolyte aluminum trifluoromethanesulfonate aqueous solution), it can be seen that: the battery exhibits a stable voltage platform of ~2V and can be cycled for ~450h, showing long-term aluminum stripping / electroplating stability compared to aluminum foil.
[0070] Fig. 9 The battery assembled with aluminum-zinc alloy (atomic ratio of 80:20) in Example 3 was tested at room temperature and 0.05 mA / cm -2 From the cycle test diagram under current density (a in the figure corresponds to the electrolyte aluminum perchlorate aqueous solution, and b in the figure corresponds to the electrolyte aluminum trifluoromethanesulfonate aqueous solution), it can be seen that: due to the inhibition of passivation, the aluminum-zinc alloy (atomic ratio of 80:20) symmetrical battery exhibits a stable voltage platform of ~2V and can be cycled for ~650h, showing long-term aluminum stripping / electroplating stability, while the symmetrical battery assembled with aluminum foil is electrochemically unstable and the degree of polarization continues to increase.
[0071] Fig.10 and Fig.11 The battery assembled with the aluminum-zinc alloy in Example 2 (atomic ratio of 90:10) and the aluminum-zinc alloy in Example 3 (atomic ratio of 80:20) was charged at room temperature and 0.2 mA / cm -2 Cyclic test diagram under current density, where Fig.10 Corresponding to aluminum perchlorate electrolyte, Fig.11 Corresponding to aluminum trifluoromethanesulfonate electrolyte. It can be seen that: due to the inhibition of passivation, the aluminum-zinc alloy (atomic ratio of 90:10) symmetric battery of Example 2 exhibits a stable voltage platform of ~2V, can be cycled for ~500h, and exhibits long-term aluminum stripping / electroplating stability; the aluminum-zinc alloy (atomic ratio of 80:20) symmetric battery of Example 3 exhibits a stable voltage platform of ~2V, can be cycled for ~550h, and exhibits long-term aluminum stripping / electroplating stability; while the symmetric battery assembled with aluminum foil can only operate stably for ~70h, after which the degree of polarization continues to increase.
[0072] Fig.12 The rate performance test diagram of the battery assembled with the aluminum-zinc alloy (atomic ratio of 90:10) in Example 2 and the aluminum-zinc alloy (atomic ratio of 80:20) in Example 3 at room temperature shows that: when the current density is increased from 0.1 mA / cm -2 , 0.2mA / cm -2 , 0.3mA / cm -2 Continue to increase to 1.6mA / cm -2 , 1.8mA / cm -2 , 2.0mA / cm -2During the process, the hysteresis voltage of the symmetrical battery of Example 2 and Example 3 was stable at ~2V without obvious voltage fluctuation, while the aluminum foil symmetrical battery was -2 Large voltage fluctuations and hysteresis occur during cycling.
[0073] 2. Full battery
[0074] The aluminum-zinc alloy microsphere (atomic ratio of 90:10) negative electrode slurry prepared in Example 2 or the zinc alloy microsphere (atomic ratio of 80:20) negative electrode slurry prepared in Example 3 was vacuum dried in an oven at 80°C for 8 hours, and then pressed into discs with a diameter of 10 mm at a pressure of 6 tons to obtain negative electrode sheets.
[0075] The phenazine derivative HH was used as the positive electrode material, mixed with polyvinylidene fluoride, Ketjen black, and N-methylpyrrolidone in a mass ratio of 6:3:1:3 to form a slurry, and coated on titanium foil with an active material loading of 0.1 mg / cm -2 , and obtain the positive electrode sheet.
[0076] The CR2032 button cell was assembled in the order of negative electrode shell-negative electrode sheet-diaphragm-electrolyte-positive electrode sheet-positive electrode shell, with glass fiber as the diaphragm and 1M aluminum trifluoromethanesulfonate aqueous solution as the electrolyte.
[0077] The assembled CR2032 button cell was charged and discharged at room temperature at a current density of 100 mA / g. Fig.13 and Fig.14 As shown, it can be seen that the first cycle discharge capacity of the button cell assembled with aluminum-zinc alloy (atomic ratio of 90:10) in Example 2 is 125 mAh / g, the specific capacity after 100 cycles is 90 mAh / g, and the capacity retention rate is 72%; the first cycle discharge capacity of the button cell assembled with aluminum-zinc alloy (atomic ratio of 80:20) in Example 3 is 170 mAh / g, the specific capacity after 100 cycles is 130 mAh / g, and the capacity retention rate is 76.5%.
[0078] The above description is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing aluminum alloy spherical powder for aluminum secondary battery negative electrode by atomization method, characterized in that: The following steps are involved: S1. According to the target composition of the aluminum alloy, various metal ingots in the aluminum alloy are mixed and smelted to obtain a molten aluminum alloy liquid; S2, atomizing the molten aluminum alloy liquid, cooling and solidifying the formed fine droplets, and then sieving to obtain aluminum alloy spherical powder.
2. The method for preparing aluminum alloy spherical powder for negative electrode of aluminum secondary battery by atomization method according to claim 1, characterized in that: The aluminum alloy includes the following components in atomic percentage: Al 60-100%, M 0-40%, wherein M is one or more of Zn, Li, Mg, Fe, Si, Mn, La, Ce, Pr, Nd, Y and Sc.
3. The method for preparing aluminum alloy spherical powder for negative electrode of aluminum secondary battery by atomization method according to claim 1, characterized in that: In step S1, the smelting is carried out under vacuum, the melt temperature is 650-800°C, and the smelting time is 1-2h.
4. The method for preparing aluminum alloy spherical powder for negative electrode of aluminum secondary battery by atomization method according to claim 1, characterized in that: In step S2, the atomization method is: the molten aluminum alloy liquid flows into the atomization nozzle through the guide pipe, and is impacted by the high-pressure gas at the atomization nozzle to form fine droplets, and the formed fine droplets are quickly cooled and solidified into aluminum alloy spherical powder.
5. The method for preparing aluminum alloy spherical powder for negative electrode of aluminum secondary battery by atomization method according to claim 4, characterized in that; The diameter of the flow guide tube is 3-7 mm, the flow rate of the molten aluminum alloy liquid is 10-15 g / s; the flow rate of the high-pressure gas is 25 m / s. 3 / h~30m 3 / h, the atomization pressure is 2.0MPa-3.0MPa, and the gas medium used is one of nitrogen, argon and helium; the cooling rate of the cooling solidification is 60-102℃ / s.
6. Aluminum alloy spherical powder obtained by the method according to any one of claims 1 to 5.
7. An aluminum secondary battery, characterized in that: The negative electrode active material of the aluminum secondary battery adopts the aluminum alloy spherical powder according to claim 6.
8. The aluminum secondary battery according to claim 7, characterized in that: The aluminum alloy spherical powder is mixed with a conductive agent and a binder in a solvent, and ground evenly to obtain a negative electrode slurry; The negative electrode slurry is uniformly coated on a current collector and dried to obtain an aluminum secondary battery negative electrode; or the negative electrode slurry is dried and then pressed into sheets to obtain an aluminum secondary battery negative electrode.
9. The aluminum secondary battery according to claim 8, characterized in that: The conductive agent is one of Ketjen black, carbon black and acetylene black, the binder is polyvinylidene fluoride or polytetrafluoroethylene, and the solvent is N-methylpyrrolidone.
10. The aluminum secondary battery according to claim 8, characterized in that: The mass ratio of the aluminum alloy spherical powder, the conductive agent, the binder and the solvent is 70-80:5-10:5-20:150-300.
Citation Information
Cited By
Continuous water atomized metal powder production apparatus
CN122722894A
